PERINEUM MASSAGE EDUCATION TO EMPOWER PREGNANT WOMEN IN PREVENTING PERINEAL RUPTURE AT PENELEH PUBLICH HEALTH CENTER SURABAYA 2023 - Kurniawati, Eighty Mardiyan; Hardianto, Gatut; Wahyuningtyas, Riska; Rahmawati, Nur Anisah; Mustofa, Vina Firmanty; Safitri, Cahyani Tiara; Kurniawan, Agde Muzaky; Rustam, Mardianti (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The three highest causes of maternal death in Indonesia, which is bleeding. Severe perineal rupture or what is called OASIS can cause bleeding that can lead to death. This community service activity aims to provide education about perineal massage to empower pregnant women to prevent perineal rupture at the Peneleh Public Health Center, Surabaya in 2023. Partnership programs are needed to achieve the Sustainable Development Goals (SDGs) targets. The problem faced by partners is that even though pregnancy classes are running, they do not yet provide material on preventing perineal rupture and practicing perineal massage so mothers do not have an understanding of techniques for preventing perineal rupture. Apart from that, health workers have not mastered perineal massage techniques so they cannot provide their knowledge to pregnant women. Activities are carried out in the form of providing material and practice. The evaluation was carried out by administering a pretest and posttest for knowledge and assessment of perineal massage skills for pregnant women and health workers. The evaluation method used was the ability of pregnant women to perform phantom perineal massage exercises. Pregnant women are said to be able to do this if they can do it correctly. Providing education related to perineal massage can increase the knowledge and skills of pregnant women thereby supporting the prevention of bleeding. Suggestions for community health centers to improve education so that pregnant women are ready to do it independently at home and provide support to health workers to provide education to pregnant women.